Change in economic policy paradigm: Privatization and state capture in Poland - Piotr Kozarzewski; Maciej Bałtowski (Center for Social and Economic Research (CASE), 2016)
Piotr Kozarzewski and Maciej Ba±towski analyse the causes and manifestations of Poland's recent shift in economic policy towards a more active role of the state, and use privatization policy as an example. The authors examine the effects of the privatization policy and point to a large unfinished agenda in ownership transformation that has had an adverse impact on the institutional setup of the Polish state, creating grounds for rent seeking and cronyism, which, in turn, impede the pace of privatization. They find out that it is the increasing capture of the state by rent-seeking groups, and not, contrary to popular opinion, the global financial crisis, that most contributes to the growing statist trends of Poland's economic policy.
Keywords: D72; L33; P16; P31; 330; Poland; privatization; economic policy; post-communist transition; crony capitalism; rent seeking; role of the state